Heart Failure and the Non-Resolution of Atrial Thrombus Detected in Anticoagulated Patients with Non-Valvular Atrial Fibrillation - Shu Yang MD; Jie Yang MM; Ning Chen MD; Chang Cui MD; Jincheng Jiao MD; Li Zhu MD; Mingfang Li MD; Minglong Chen MD (Clinical and Applied Thrombosis/Hemostasis)
Background To investigate the relationship between heart failure (HF) and the non-resolution of atrial thrombus detected in anticoagulated patients with non-valvular atrial fibrillation (NVAF). Methods This was a single-center, observational, retrospective, and prospective study. Anticoagulated patients with NVAF and atrial thrombus identified by transesophageal echocardiography or cardiac computed tomography angiography were consecutively enrolled. All patients received follow-up imaging within 6 months to assess the resolution of atrial thrombus. The primary endpoint was the resolution of atrial thrombus and the secondary endpoint was the occurrence of ischemic stroke, major bleeding, and all-cause death during the follow-up period. Results Among 8987 patients with NVAF scheduled for catheter ablation or cardioversion, 70 anticoagulated patients with atrial thrombus were final analyzed. The average age was 61.8±10.6 years, 62.9% of them were men, and 32 (45.7%) patients presented with HF. Within the 6-month follow-up period, atrial thrombus resolution was observed in 47 (67.1%) patients. The rate of atrial thrombus resolution was lower in patients with baseline HF (50.0% vs 81.6%). In the adjusted logistic regression analysis model, HF was independently associated with the non-resolution of atrial thrombus (adjusted OR: 5.38, 95% CI: 1.19-24.27). During the median follow-up period of 4.5 years, four ischemic stroke events occurred in four patients. None of the patients in this study experienced major bleeding events or death during follow-up. Conclusions HF was associated with the non-resolution of atrial thrombus detected in anticoagulated patients with NVAF. Further research is needed to identify optimal therapeutic approaches for this high-risk population.